Accounting for sleep loss in early modern England. Issue 3 (17th April 2020) - Handley, Sasha
Abstract : How did people in the sixteenth and seventeenth centuries account for sleep loss? This article answers this question through an in-depth analysis of the life-writings of six early modern women and men that suffered from periodic or persistent episodes of sleep loss. It focuses on the ways in which these health crises were understood to impede the ordinary functions of body and mind, while also revealing how gendered discourses of illness shaped female and male explanations of sleep loss in different ways. The article is the first to identify early modern sleep loss as an acknowledged cause of poor mental health. It also sheds important light on how the distinctive medical culture of the period ca 1500–1700 encouraged ordinary householders to protect the quality of their sleep by moderating their bedtimes, diets, emotions, and by preparing soporific remedies for the home. This evidence shows that restorative sleep was treasured as an unparalleled guardian and barometer of physical, mental and spiritual health.